1986
DOI: 10.1161/01.hyp.8.6_pt_2.ii61
|View full text |Cite
|
Sign up to set email alerts
|

The loss of endothelium-dependent vascular relaxation in hypertension.

Abstract: We investigated endothelium-dependent relaxation in rat aortae, using three models of experimental hypertension: deoxycorticosterone and salt; one-kidney, one clip renovascular hypertension; and coarctation. Isolated aortae were contracted with phenylephrine, and relaxation was subsequently induced with acetylcholine or calcium ionophore A23187. Blood vessels denuded of endothelium did not relax in response to acetylcholine or A23187. Blood vessels from animals with high blood pressure had decreased relaxation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
138
4
2

Year Published

1991
1991
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(157 citation statements)
references
References 9 publications
13
138
4
2
Order By: Relevance
“…16,17 Our recent studies indicate that endothelin-1 (ET-1) plays an important role in NADPH oxidase-derived O 2 Ϫ production in this model. [13][14][15] However, the interaction between ET-1-induced O 2 Ϫ and BH 4 on endothelial dysfunction and the underlying mechanisms are unknown.…”
Section: T Etrahydrobiopterin (Bhmentioning
confidence: 88%
“…16,17 Our recent studies indicate that endothelin-1 (ET-1) plays an important role in NADPH oxidase-derived O 2 Ϫ production in this model. [13][14][15] However, the interaction between ET-1-induced O 2 Ϫ and BH 4 on endothelial dysfunction and the underlying mechanisms are unknown.…”
Section: T Etrahydrobiopterin (Bhmentioning
confidence: 88%
“…For example, in hypercholesterolemic rabbits with impaired endothelial relaxation, NO bioavailability was decreased because of oxidation of NO into vasoinactive nitrates/nitrites, and treatment with SOD reversed endothelial dysfunction (225). Other animal models also demonstrate increased degradation of NO as the cause of endothelial dysfunction and hypertension (192). eNOS is a cytochrome p450 reductase-like enzyme that catalyzes flavin-mediated electron transport from the electron donor NAD(P)H to a prosthetic heme group.…”
Section: High Saltmentioning
confidence: 99%
“…Lockette et al (1986) reported that endothelium-dependent responses could be 'normalized' in aortic rings of hypertensive rats after lowering of blood pressure. This argument is probably not applicable in our study because the blood pressure changes were relatively small.…”
Section: Plasma Electrolytesmentioning
confidence: 99%